Analysis of the regional economic structure of the Tacna-Arica bi-border area (2007-2017) - Palza Chambe, Edwin Ismael (2021)
Since 1929, when the border treaty between Peru and Chile was signed, determining that Tacna would return to Peruvian possession and Arica would continue to be administered by the Chilean government, a common space that was synergistically emerging as one of the most important in the Pacific was broken up. This generated the deterioration of the economy of both regions, which were also aggravated by the contextual conditions and the exposure to major crises present throughout most of the 20th century. The regional analysis technique methodology made it possible to determine the retraction of the dynamics of the Tacna region and the growth of that observed inArica and Parinacota in the 2007-2017 period of analysis, an expansion sustained fundamentally by the cyclical growth of sectors such as mining and government work, which incorporated an important proportion of the economically active population of this region.